Not a Quiet Place: Understanding Noise Level in a Newborn Intensive Care Unit (NICU) and Its Relation with Newborn’s Vital Parameters, a Pilot Feasibility Study - Silvia Rossi; Alessia Salvatore; Giulia Ottonello; Ilaria Artuso; Roberta Da Rin Della Mora; Simona Serveli; Silvia Scelsi (Children)
Background/Objectives: Adaptation to extrauterine life is challenging for preterm newborns. Environmental stimuli, such as noise, can lead to adverse health outcomes, causing instability of vital parameters and impairment of neurodevelopment. The American Academy of Pediatrics recommends a maximum environmental noise level of 45 decibels (dB) or less in the NICU. The study’s primary aim was to describe environmental noise in a neonatal intensive care unit and to analyze potential associations between noise and vital parameters of preterm newborns, including heart rate, respiratory rate, and oxygen saturation levels. Methods: A pilot observational feasibility study was conducted in a level III NICU. Sound levels and vital parameters were recorded over four hours for each preterm newborn. Confounding variables were controlled. Data were analyzed using descriptive statistics, Kendall’s τ-b, and logistic regression analysis. Ethical approval and parental consent were obtained. Results: The average environmental noise level was consistently above 45 dB. Six patients were enrolled, and 22 recordings (ranging in length from 1 to 4 h) were performed. Data adjusted for confounding variables show a statistically significant Kendall’s correlation between heart rate and decibels (τ-b = 0.89, p = 0.003, n = 520), suggesting a monotonous crescent tendency between these two variables, although the relationship is not strong. The logistic regression model indicates that the odds ratio (OR) for decibels related to tachycardia is 1.066, meaning that for each 1 dB increase, the probability of tachycardia rises by 6.6% (p < 0.001). Conversely, the OR for respiratory rate is 0.959, suggesting that for each unit increase in respiratory rate, the probability of tachycardia decreases by approximately 4.1% (p < 0.001). Conclusions: The study reveals that the mean environmental noise level in the NICU consistently exceeds the recommended safety level. Decibels are one of the significant variables contributing to the likelihood of tachycardia, and an increase in decibels has a significant effect on this, but it is not the only one. Further analysis of a larger sample is needed.